Z ustreznimi pristopi do preoblikovanja alternativnih pojmovanj - Dolenc-Orbanić, Nataša (Vodenje v vzgoji in izobraževanju, 2015)
Learning is viewed as a dynamic process of changing, reconstructing and forming notions and concepts, which requires the teacher to know when and how students learn concepts, since it is the way they are taught that influences the way the students will understand, use and incorporate these concepts into their existing experience. It is inevitable that children often form the so-called alternative notions and concepts that are incomplete or even incorrect. At first, these emerge spontaneously from different personal experiences, but they also take shape in schools, especially due to inadequate explanations as provided by the teacher, and the professionally incorrect or misleading clarifications of concepts as they appear in study materials. Thusly formed conceptualisations are often deeply rooted, they present a great obstacle for learning, and frequently prove difficult to reshape by means of traditional teaching strategies. Conversely, by using modern teaching approaches aimed at active knowledge construction, students are provided with opportunities to abandon their alternative understandings and replace them with new ones that are closer to scientific truths. In regard to the issue under discussion, this article presents some specific cases of how and why such incorrect conceptualisations emerge and through what approaches they can be reshaped, since the concept shaping is one of the fundamental tasks of instruction.
Keywords: alternative understandings; constructivist approach; konstruktivistični pristop; naravoslovje; natural science classes; osnovne šole; pouk; učne metode